Memory: An Extended Definition - Zlotnik, Gregorio; Vansintjan, Aaron (Frontiers in Psychology, 2019)
Recent developments in science and technology point to the need to unify, and extend, the definition of memory. On the one hand, molecular neurobiology has shown that memory is largely a chemical process, which includes conditioning and any form of stored experience. On the other hand, information technology has led many to claim that cognition is also extended, that is, memory may be stored outside of the brain. In this paper, we review these advances and describe the increasingly accepted extended definition of memory. This definition is largely accepted in neuroscience but not explicitly stated. In the extended definition, memory is the capacity to store and/or retrieve information. Does this new definition of memory mean that everything is now a form of memory? We stress that memory still requires incorporation, that is, a corpore. It is a relationship -- where one biological or chemical process is incorporated into another, and changes both in a permanent way. Looking at natural and biological processes of incorporation can help us think of how incorporation of internal and external memory occurs in cognition. We further argue that, if we accept that there is such a thing as the storage of information outside the brain -- and that this organic, dynamic process can also be called “memory” -- then we open the door to a very different world. The mind is not static. The brain, and the memory it uses, is a work in progress; we are not now who we were then.